Spectrophotometric determination of nevirapine using tetrathiocyanatocobalt(II) ion as a reagent - Sreevidya, Thekke V.; Narayana, Badiadka (Eclética Química, 2010)
A simple and rapid spectrophotometric method for the determination of nevirapine is described. The method is based on the reaction of nevirapine with tetrathiocyanatocobalt(II) ion in buffer of pH 4 to form the corresponding complex. Beer’s law is obeyed in the range of 0.2 – 2.0 μg mL-1 for nevirapine. The optical parameters such as molar absorptivity, Sandell’s sensitivity, detection limit and quantitation limit were found to be 1.16× 104 Lmol-1cm-1, 2.09 X 10-3 μg cm-2, 0.073 μg mL-1 and 0.222 μg mL-1 respectively. The optimum reaction conditions and other analytical parameters were evaluated. The statistical evaluation of the method was examined by determining intra-day and inter-day precision. The proposed method has been successfully applied for the determination of nevirapine in pharmaceutical formulations.